SURVEY OF WATER BORNE PROTOZOAN PARASITES IN DRINKING WATER SOURCES OF SOME SELECTED COMMUNITIES IN GOMBE METROPOLIS, GOMBE STATE - AYUBA, JEMIMAH; KHADIJAT, ADEYEMI ADEDOLAPO; TELA, MURNA; ASHER, REJOICE (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
The aim of this research is to access the availability of different types of water borne protozoan parasites and the impact on the overall health of the people in communities within the study area. A survey of different water sources was conducted for possible water borne protozoan parasites and the impact on the overall health of the people in communities within the study area. The study was carried out in four different communities within Gombe metropolis. Microscopic examination of the sediments after centrifugation of the water samples was the principal method employed in the analysis. A retrospective study was conducted at different primary health care centers within the communities. In order to ascertain the incidence of water borne infections in the study area, hospital records kept in the health centers were used. Case notes of subjects from 2016 to 2018 in each of the community was considered. The case notes were assessed for diagnosis of various water related infections. Out of the 100 water samples collected and examined, 86 samples were positive with protozoan parasites. The result of the study indicate that water from well is the most contaminated (46.64 %). Three different protozoan parasites were identified; this include Giardia lamblia, Cryptosporidium parvum and Entamoeba histolytica. Giardia lamblia was the most prevalent. The result of the retrospective study conducted at different primary health care centers from 2016 to 2018 indicates a progressive decrease in the number of patients with reported complaints of water related diseases. The highest complaint diagnosed cases was recorded in 2017. Age distribution of water-borne related infections cases revealed the highest incidence among the age group of 10-15 years. The protozoan parasites encountered were noted to affect human health. As such, public education on the importance of personal hygiene and optimal environment sanitation have been recommended.